2004
DOI: 10.1152/ajpcell.00226.2004
|View full text |Cite
|
Sign up to set email alerts
|

Real-time three-dimensional imaging of lipid signal transduction: apical membrane insertion of epithelial Na+ channels

Abstract: In the distal tubule, Na(+) resorption is mediated by epithelial Na(+) channels (ENaC). Hormones such as aldosterone, vasopressin, and insulin modulate ENaC membrane targeting, assembly, and/or kinetic activity, thereby regulating salt and water homeostasis. Insulin binds to a receptor on the basal membrane to initiate a signal transduction cascade that rapidly results in an increase in apical membrane ENaC. Current models of this signaling pathway envision diffusion of signaling intermediates from the basal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…However, PI(3,4,5)P 3 should first be produced in the inner leaflet of the basolateral membrane and then diffused in the inner leaflet to the apical membrane because the PI3K inhibitor LY294002 was added to the basolateral bath. This hypothesis is supported by previous studies, which showed that PI(3,4,5)P 3 can laterally diffuse in the inner leaflet of epithelial cell membranes from the basolateral membrane domain, where it is generated, to the apical membrane domain (30). Theoretically, the apical PI(3,4,5)P 3 would be rapidly degraded because the lipid phosphatase PTEN (phosphatase and tensin homolog) is located in the apical membrane (31).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, PI(3,4,5)P 3 should first be produced in the inner leaflet of the basolateral membrane and then diffused in the inner leaflet to the apical membrane because the PI3K inhibitor LY294002 was added to the basolateral bath. This hypothesis is supported by previous studies, which showed that PI(3,4,5)P 3 can laterally diffuse in the inner leaflet of epithelial cell membranes from the basolateral membrane domain, where it is generated, to the apical membrane domain (30). Theoretically, the apical PI(3,4,5)P 3 would be rapidly degraded because the lipid phosphatase PTEN (phosphatase and tensin homolog) is located in the apical membrane (31).…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies suggested that PI(3,4,5)P 3 is produced in the inner leaflet of the basolateral membrane and can freely diffuse in the inner leaflet to reach the apical membrane (30). Therefore, the PI3K inhibitor was added to the basolateral bath.…”
Section: Inhibition Of Pi3k Abolishes the Effect Of H 2 O 2 On Enac Pmentioning
confidence: 99%
“…The effects of aldosterone and insulin or IGF-1 may be additive [17]. Insulin stimulates SGK1 and is thus expected to enhance ENaC activity and renal Na + reabsorption [6][7][8]. SGK1 contributes to the regulation of renal Na + excretion by aldosterone, insulin, and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Because insulin also elevates ENaC activity via PI 3-K (28,42), PIP 3 likely also mediates the regulation of ENaC by insulin (43,44).…”
Section: Stimulation Of Steroid Receptors Increases Membrane Pip 3 Anmentioning
confidence: 99%
“…Using this method, recent studies have shown that there is an obvious elevation of apical membrane PIP 3 in response to insulin (43). We recently demonstrated that both PIP 3 and the N-terminal tail of ␥-ENaC are required for aldosteroneinduced ENaC activity and trafficking (62).…”
Section: Possible Role Of Pip 2 and Pip 3 In Receptormediated Enac Rementioning
confidence: 99%